2017
DOI: 10.1016/j.solmat.2016.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of all-angle black surfaces for silicon solar cells

Abstract: Abstract-Optical losses at the front surface of a silicon solar cell have a significant impact on efficiency, and as such, efforts to reduce reflection are necessary. In this work, a method to fabricate and passivate nanowire-pyramid hybrid structures formed on a silicon surface via wet chemical processing is presented. These high surface area structures can be utilised on the front surface of back contact silicon solar cells to maximise light absorption therein. Hemispherical reflectivity under varying incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 39 publications
(46 reference statements)
2
29
0
Order By: Relevance
“…However, the above technologies employ sophisticated equipment that predetermines high cost of the resulting product. It is possible to reduce the cost of SC along the way of forming the layers of porous silicon (PS) of the "Black Si" type by using electrochemical etching [3,4]. All these factors need to be considered when choosing the technological method for obtaining the front surface of SC.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, the above technologies employ sophisticated equipment that predetermines high cost of the resulting product. It is possible to reduce the cost of SC along the way of forming the layers of porous silicon (PS) of the "Black Si" type by using electrochemical etching [3,4]. All these factors need to be considered when choosing the technological method for obtaining the front surface of SC.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…[6][7][8] On the other hand, as the alternative transparent electrode, graphene transfer on cell has unique advantages such as low cost, high performance and simple process. Therefore, many studies focus on graphene/Si schottky junction solar cell with wet transfer graphene process in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that SiNW arrays have high light absorptance and are promising as absorber layers for solar cells. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, despite their excellent optical advantages, the conversion efficiency of SiNW-based solar cells is yet insufficient because of serious surface recombination due to their high surface area-to-volume ratio. Accordingly, it is necessary to obtain high absorptance with short wires from the perspective of not only an etching margin but also surface recombination.…”
Section: Introductionmentioning
confidence: 99%